PENGHITUNGAN KERUGIAN KEUANGAN NEGARA OLEH KANTOR AKUNTAN PUBLIK DALAM PERKARA TINDAK PIDANA KORUPSI (Studi : Putusan Pengadilan Tipikor Pada Pengadilan Negeri Medan No. 93/Pid.Sus-TPK/2016/PN.Mdn., tertanggal 16 Februari 2017) - Muhammad Isnayanda; Alvi Syahrin; Madiasa Ablisar; Muhammad Ekaputra (USU LAW JOURNAL, 2018)
ABSTRACT The case of corruption is a major problem in Indonesia that causes a huge loss of state and affects the decline in the quality of people's lives to disrupt economic stability. In the case of corruption (hereinafter called "Corruption"), as for the authorities to conduct an investigation under the applicable law, among others: the Indonesian Police, the Attorney General's Office and the Corruption Eradication Commission. Based on the authority given by the law mentioned above, to every investigator and investigator to conduct a corruption investigation and investigation, the Police of the Republic of Indonesia, the Attorney General of Indonesia and the Corruption Eradication Commission have the authority to conduct investigation and investigation of Corruption. In the eradication of corruption, the government has promulgated Law no. 31 of 1999 on the Eradication of Corruption as amended by Act No. 20 of 2001 on Amendment to Law no. 31 Year 1999 on the Eradication of Corruption (hereinafter referred to as "Corruption Act"). The most important element of the article in the Corruption Act is "it can harm the state's finances or the state's economy". Thus, the calculation of State Financial Losses (PKKN) is needed in conducting investigations and investigations in cases of corruption. Keywords : Calculation of State Financial Losses; Public Accountant Office / Public Accountant; Case of Corruption.